2017
DOI: 10.1007/164_2017_73
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Drug Binding to Voltage-Gated Sodium Channels

Abstract: Voltage-gated sodium (Na) channels are expressed in virtually all electrically excitable tissues and are essential for muscle contraction and the conduction of impulses within the peripheral and central nervous systems. Genetic disorders that disrupt the function of these channels produce an array of Na channelopathies resulting in neuronal impairment, chronic pain, neuromuscular pathologies, and cardiac arrhythmias. Because of their importance to the conduction of electrical signals, Na channels are the targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 140 publications
0
10
0
Order By: Relevance
“…Class IB drugs (lidocaine) on the other hand bind to the channel in both the open and the inactivated states and block the channel by stabilizing the inactivated/closed state ( Bean et al, 1983 ; Pless et al, 2011 ). Detailed discussion on molecular determinants of state-dependent drug binding in the central cavity can be found in ( O'Leary and Chahine, 2018 ).…”
Section: Natural Druggability Of Voltage-gated Sodium Channelsmentioning
confidence: 99%
“…Class IB drugs (lidocaine) on the other hand bind to the channel in both the open and the inactivated states and block the channel by stabilizing the inactivated/closed state ( Bean et al, 1983 ; Pless et al, 2011 ). Detailed discussion on molecular determinants of state-dependent drug binding in the central cavity can be found in ( O'Leary and Chahine, 2018 ).…”
Section: Natural Druggability Of Voltage-gated Sodium Channelsmentioning
confidence: 99%
“…Nav activities control not only basic impulse generation and conduction but also directional and patterned growth, including target-speci c axonal migration and regional synaptic connectivity [30][31][32]. Nav has also been related to several hereditary diseases of excitable tissues [30,33], and more complicated pathological disorders, including chronic pain syndromes [34], epilepsy [35], ischaemic stroke[36], and Alzhei-mer's disease [37]. Some studies have shown that the expression of α and β subunits of Nav was upregulated in various cancers including prostate, lung, and cervical cancer, which has been observed both in vitro and in vivo systems [29,[38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Disruptions to inactivation through mutations or other manipulations have previously been shown to weaken binding of local anesthetics to Na v channels ( 45 , 46 ). This is in line with our finding that quinidine has lower apparent affinity on the WT phY background than on the WT NM background, as the former displays an 11-mV right-shift in SSI.…”
Section: Discussionmentioning
confidence: 99%